Evidence for a 'plant community economics spectrum' driven by nutrient and water limitations in a Mediterranean rangeland of southern France - Pérez-Ramos, Ignacio M.; Roumet, Catherine; Cruz, Pablo; Blanchard, Alain; Autran, Paul; Garnier, Eric (The Journal of ecology, 2012)
1. Plant species composition and community functional structure (i.e. trait composition at the community level) result from a hierarchy of environmental filters that constrain which species and traits tend to be dominant in a given habitat. 2. We quantified variation in community functional structure along natural gradients of soil resources using several above- and below-ground parameters and explored links among these attributes to determine whether plant resource economics can be applied at the community level in a Mediterranean rangeland of southern France. 3. Limitation by nitrogen, soil water and soil depth were the main ecological factors driving the functional response at the community level. Most of the community functional parameters considered in this study were more dependent on nitrogen limitation than on the other two factors, mostly related with the acquisition—conservation trade-off at both the leaf and the root level. 4. We found a strong coordination between above-ground and below-ground components, with a high level of concordance along the resource gradients explored. As an example, tissue dry matter content — both in leaves and roots — was positively related to nitrogen limitation. These findings indicate that the leaf economic spectrum paradigm (resource conservation in resource-poor habitats versus resource acquisition in resource-rich habitats) can be extrapolated to the below-ground component and extends to a plant community spectrum. 5. Changes in the functional structure of communities were promoted by two complementary components of variation: (i) the replacement of species with highly contrasting resource-use strategies and, to a lesser extent, (ii) the intraspecific variation in several above-ground traits. 6. Synthesis. This study showed that soil water and nutrient limitations are the main drivers controlling functional community structure in the Mediterranean rangelands studied and that shifts in this structure were mainly due to species turnover. In addition, we provided evidence for a plant community economics spectrum, based on a strong coordination between above- and below-ground components in these resource-limited communities.